Modelos matemáticos para estimativa do consumo máximo de oxigênio pela ventilometria de esforço em indivíduos saudáveis - Barbosa, Fernando Policarpo (2007)
The relation between metabolic demand and maximal oxygen consumption during exercise have been investigated in different areas of knowledge. In the health field, the determination of maximal oxygen consumption (VO2max) is considered a method to classify the level of physical fitness or the risk of cardiocirculatory diseases. The accuracy to obtain data provides a better evaluation of functional responses and allows a reduction in the error margin at the moment of risk classification, as well as, at the moment of determination of aerobic exercise work load. In Brasil, the use of respirometry associated to ergometric test became an opition in the cardiorespiratory evaluation. This equipment allows predictions concerning the oxyredutase process, making it possible to identify physiological responses to physical effort as the respiratory threshold. This thesis focused in the development of mathematical models developed by multiple regression validated by the stepwise method, aiming to predict the VO2max based on respiratory responses to physical effort. The sample was composed of a ramdom sample of 181 healthy individuals, men and women, that were randomized to two groups: regression group and cross validation group (GV). The voluntiars were submitted to a incremental treadmill test; objetiving to determinate of the second respiratory threshold (LVII) and the Peak VO2max. Using the método forward addition method 11 models of VO2max prediction in trendmill were developded. No significative differences were found between the VO2max meansured and the predicted by models when they were compared using ANOVA One-Way and the Post Hoc test of Turkey. We concluded that the developed mathematical models allow a prediction of the VO2max of healthy young individuals based on the LVII